Igniting Innovation : Rethinking the Role of Government in Emerging Europe and Central Asia - Goldberg, Itzhak; Goddard, John Gabriel; Kuriakose, Smita; Racine, Jean-Louis (World Bank, 2012)
This book builds on the lessons from public institutions and programs to support innovation, both successful and failed, from Europe and Central Asia (ECA) as well as China, Finland, Israel, and the United States. Field visits to these countries were hosted by the innovation and scientific agencies of the respective governments, strengthening the international experiences presented here. This book is a culmination of ten years of analytic and operational work led by the private and financial sector development department and the chief economist's office of the ECA region of the World Bank. Several regional reports and country policy notes exploring these issues have been published over the years. The book also reflects the lively discussion in the ongoing series of flagship events to promote knowledge based economies in the region. The most recent knowledge economy forum was held in Berlin in 2010, hosted by the fraunhofer center for Central and Eastern Europe. The book identifies policies that have an adverse affect on innovation. It also identifies policy gaps that, if filled, could have a catalytic effect on private sector innovation.